Artificial intelligence techniques in power systems - Warwick, Kevin 1954-; Ekwue, Arthur; Aggarwal, Raj (Institution of Engineering and Technology, 1997)
In the field of power systems one of the most exciting and potentially profitable recent developments is the increasing use of artificial intelligence techniques in monitoring, control and assessment. As a result of this, it was felt timely for a series of related articles to be put together to form a comprehensive guide which can serve as a reference text in the area. This book certainly serves as such a text. The intention of the book is to give an introduction to, and an overview of, the field of artificial intelligence techniques in power systems, with a look at various application studies. The book should therefore be useful to a range of readers; including practising power systems engineers, researchers in the field and those studying the use of artificial intelligence. In its entirety the book gives an up-to-date, broad coverage of the possible uses of artificial intelligence in a power systems environment, as well as an indication of recent research progress. The book could easily be used as a comprehensive text giving a fair coverage of different aspects of the field or rather in terms of the individual chapters, each of which deals with a specific topic in depth. The intention is that the book is of use as much to those from a power systems background who wish to find out about how artificial intelligence techniques could be of use, as it is to those from an artificial intelligence background who would like to find out more about the specific power systems application area.